Analysis of banks’ systemic risk contribution and contagion determinants through the leave-one-out approach - Zedda, Stefano; Cannas, Giuseppina (Journal of Banking & Finance, 2020)
In this paper we develop an in-depth analysis of the systemic risk and contagion determinants through the differential effects of excluding one bank on the banking system. The measure allows for splitting the contribution of individual banks into systemic risk as the sum of two components—the stand-alone bank risk and the contagion risk—and measuring the role of assets, riskiness, capitalization, and interconnectedness as determinants of each of the two components. Results show that the variables determining the stand-alone risk component are different from those determining the contagion risk component, so that a bank which is relatively safe with respect to stand-alone risk, can be an important contagion vehicle, or vice versa. Results also show that crisis severity significantly affects results, so that the severity of different crises results in different weights for the input variables and different contributions for the banks considered. These results add highly significant information for macroprudential regulation, not only from the cross-sectional point of view, but also with reference to the time dimension.